Environmental History of Botanical Exchanges in the Indian Ocean World. (1st August 2012) - Rangan, Haripriya; Carney, Judith; Denham, Tim
Abstract : Much of the environmental history literature on plant transfers has centred on European agency and on the effects on both Old and New Worlds colonised and inhabited by European powers over the past five centuries. The emphasis on European agency obscures, or diverts attention from, prehistoric botanical exchanges, i.e., plants transferred by human agency from one region to another thousands of years ago. While these exchanges may not have constituted 'ecological imperialism' the plants transferred nevertheless had significant impacts on the landscapes and societies they entered and in which they became established. This paper focuses on food crop exchanges in the Indian Ocean World. It draws on recent interdisciplinary research in archaeobotany and palaeoclimatic studies to illustrate the plant transfers that took place between eastern Africa, southern Asia and mainland and Island Southeast Asia between 2500 BCE and 100 CE and to explore how these arrivals may have transformed host societies and environments.